Um estudo sobre os impactos dos relacionamentos sociais na avaliação do mérito científico - Guedes, André Calisto Souza Medeiros (2014)
Social network analysis techniques can be used to extract knowledge from the network by analyzing the interactions between its members. In this work we intend to apply echniques of social network analysis on networks formed through scientific collaborations among researchers. Our objective with this study is to analyze if these collaboration connections may have any influence in the evaluation of scientific merit. We will focus our work on two specific scenarios. The first scenario targets the evaluation of individual merit for granting scholarships to researcher and is conducted by CNPQ, the Brazilian Research Council. The second scenario focus on the evaluation of graduate programs in the country and is conducted by CAPES, the governmental body entitled to evaluate and coordinate the graduate education program in Brazil. On both scenarios we will restrict our analysis to the Computer Science area.